THE EUROPEAN COURSE AS A THREAT TO THE STATEHOOD OF MOLDOVA. HISTORICAL AND LEGAL ASPECTS - KARAMAN Alexander Akimovich (Правовое государство: теория и практика)
Since 2009, the Republic of Moldova has embarked on European integration. This course was intended to replace the failed attempt to unite with Romania, undertaken in the early years of Moldova’s sovereignty and independence at the first peak of pro-Romanian nationalist activities. There is currently a second wave of unionist actions. Romania is involved in these actions, as well. For the first time its assistance was expressed in the participation of experts from various state structures in the preparation of normative acts of the state authorities of the Moldavian SSR, then Moldova, which proclaimed the sovereignty and independence and changed the state symbols of the republic. At present, its assistance is expressed in the fact that Moldova is directly governed by Romanian citizens. This year, official statements have been made that Moldova can integrate into European structures without Transnistria. The relevance of this study is due to recent events in Moldova, including the referendum, according to the results of which, supporters of Moldova’s integration into European structures won with a negligible margin. The research uses historical and retrospective, systematic, analysis and synthesis, interpretation and other research methods. The author concludes that the implementation of de facto and de jure renunciation of Transnistria at this stage leads to the possible integration and option of Moldovia into Romania, therefore to the loss of Moldova’s statehood. The novelty of the study consists in the fact that it provides a legal analysis of the Romanianization of Moldova through the activity of its top leadership and public authorities, taking into account the results of the referendum held in Moldova on Oct ober 20, 2024.